Brief review on petroleum coke and biomass/coal co-gasification: Syngas production, reactivity characteristics, and synergy behavior. (15th November 2021) - Wang, Miao; Wan, Yiling; Guo, Qinghua; Bai, Yonghui; Yu, Guangsuo; Liu, Yurong; Zhang, Hong; Zhang, Shu; Wei, Juntao
Highlights: Research on reactivity, syngas production and synergy of petcoke-coal/biomass co-gasification are reviewed. Catalytic/non-catalytic synergy mechanisms of co-gasification reactivity and syngas production are discussed. Future perspectives on petcoke and coal/biomass co-gasification are proposed based on the lack of current research. Abstract: Petroleum coke and biomass/coal co-gasification is a promising approach for efficiently integrating the individual advantages of different gasification feedstocks with syngas production. Therefore, research on syngas production, reactivity characteristics, and synergy behavior of co-gasification is critical. In this review, the main reaction processes during co-gasification were described and the influencing factors for syngas production and reactivity characteristics of co-gasification were summarized. Moreover, the non-catalytic/catalytic synergy mechanisms in co-gasification were also discussed in detail. H2 -rich syngas derived from co-gasification could be acquired in case of (i) feedstock with high H/C ratio or alkali and alkaline earth metals (AAEMs) concentrations, (ii) high coal/biomass proportion in blends, (iii) relatively low gasification temperature, and (iv) low O2 concentration or high steam concentration in gasification agent. Higher co-gasification reactivity could be acquired in case of (i) coal/biomass with more disordered carbon structures, more developed pore structures and higher AAEMs concentrations, (ii) higher coal/biomass proportion in blends, (iii) higher gasification temperature, and (iv) higher O2 or steam concentration in gasification agent. The synergy behavior on co-gasification reactivity varied as reaction proceeded. The synergy mechanism of co-gasification showed great relationships with the migration and transfer of free radical and inherent AAEMs. The limitations and challenges within this research field were also addressed. For instance, the transfer and migration mechanisms of free radicals and AAEMs during co-gasification, and kinetics models involving parameters related to synergy behavior.